Theory in practice: identifying theory-based techniques in health coaches' tailored feedback during a weight loss intervention. Issue 11 (1st November 2020) - Ryan, Kathleen; Murphy, Lisa Ellen; Linehan, Conor; Dockray, Samantha
Abstract: Objective: A taxonomy of ninety-three functionally different behaviour change techniques (BCTs) has been identified. However, it is not fully clear how these and other theory-based techniques are applied in the day-to-day practice of people delivering health behaviour change interventions. This study examines feedback provided by expert health coaches in a behavioural weight-loss intervention, to describe; a) what theory-based techniques are used in sessions, b) which techniques are used most frequently, c) what occurs in sessions, beyond existing theory-based techniques. Main Outcome Measures: Theory-based techniques (BCTs/tailoring strategies); relational/content-based techniques. Design: 10 tailored feedback videos from two health coaches were coded using a hybrid thematic analysis approach. Theory-based techniques were coded deductively; content not matching definitions of theory-based techniques but that addressed a determinant of behaviour change were coded inductively and relational codes were connected into themes. Results: Seventeen BCTs were coded M = 20.88 times (range:1–109). Eight tailoring techniques were coded M = 25.25 times (range:1–91). Relational themes included; 'Autonomous interpersonal coaching style, ' 'Supportive accountability, ' and 'Coach as expert'. Additional behavioural techniques were also identified. Conclusion: This work highlights what and how theory-based techniques are implemented in a weight-loss intervention, drawing attention to the role of tailoring techniques and health coaches in supporting behaviour change.